Human papillomavirus‐based screening at extended intervals missed fewer cervical precancers than cytology in the HPV For Cervical Cancer (HPV FOCAL) trial. Issue 6 (10th May 2022) - Gottschlich, Anna; Gondara, Lovedeep; Smith, Laurie W.; Cook, Darrel; Martin, Ruth Elwood; Lee, Marette; Peacock, Stuart; Proctor, Lily; Stuart, Gavin; Krajden, Mel; Franco, Eduardo L.; van Niekerk, Dirk; et al.
Abstract: While cervix screening using cytology is recommended at 2‐ to 3‐year intervals, given the increased sensitivity of human papillomavirus (HPV)‐based screening to detect precancer, HPV‐based screening is recommended every 4‐ to 5‐years. As organized cervix screening programs transition from cytology to HPV‐based screening with extended intervals, there is some concern that cancers will be missed between screens. Participants in HPV FOr CervicAL Cancer (HPV FOCAL) trial received cytology (Cytology Arm) at 24‐month intervals or HPV‐based screening (HPV Arm) at 48‐month intervals; both arms received co‐testing (cytology and HPV testing) at exit. We investigated the results of the co‐test to identify participants with cervical intraepithelial neoplasia grade 2 or higher (CIN2+) who would not have had their precancer detected if they had only their arm's respective primary screen. In the Cytology Arm, 25/62 (40.3%) identified CIN2+s were missed by primary screen (ie, normal cytology/positive HPV test) and all 25 had normal cytology at the prior 24‐month screen. In the HPV arm, three CIN2+s (3/49, 6.1%) were missed by primary screen (ie, negative HPV test/abnormal cytology). One of these three misses had low‐grade cytology findings and would also not have been referred to colposcopy outside of the trial. Multiple rounds of cytology did not detect some precancerous lesions detected with one round of HPV‐based screening. In our population, cytology missed more CIN2+, even at shorter screening intervals, than HPV‐based screening. This assuages concerns about missed detection postimplementation of an extended interval HPV‐based screening program. We recommend that policymakers consider a shift from cytology to HPV‐based cervix screening. Abstract : What's new? Human papillomavirus (HPV)‐based testing for cervical cancer is more sensitive than cytology in screening programs. However, there is persisting concern that HPV‐based cervix screening at 4‐ to 5‐year intervals could miss cancers otherwise detected by cytology at 2‐ to 3‐year intervals. This is the first study to use co‐testing 4 years after primary cytology‐ or HPV‐based screening to identify precancers that would be missed by cytology‐ or HPV‐based screening alone. Over eight times more precancers were missed by cytology‐based screening every 2 years compared to HPV‐based screening every 4 years, supporting an extended shift from cytology to HPV‐based cervix screening.